1995
DOI: 10.1093/oxfordjournals.humrep.a135864
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte and embryo quality as well as pregnancy rate in intracytoplasmic sperm injection are not affected by high follicular phase serum progesterone

Abstract: The effect of elevated serum progesterone concentrations (> 1 ng/l) on or before the day of human chorionic gonadotrophin (HCG) injection on the outcome of women receiving gonadotrophin-releasing hormone analogue (GnRHa)/human menopausal gonadotrophin (HMG) for ovarian stimulation prior to intracytoplasmic sperm injection (ICSI) was evaluated. A total of 1275 ICSI cycles were analysed retrospectively. In 53 cycles (4.5%), serum progesterone concentrations were > 1 ng/ml. Patients in the high progesterone group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…In this study, we measured the incidence of premature luteinization and its possible effect on IVF outcomes in a large population of PCOS patients. The incidence of premature luteinization ranges from 2 % to 40 % in IVF general patients [4,[25][26][27]. Bosch et al reported frequent premature luteinization and diminished PR with the introduction of a GnRH antagonist to their COH protocol for IVF in patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we measured the incidence of premature luteinization and its possible effect on IVF outcomes in a large population of PCOS patients. The incidence of premature luteinization ranges from 2 % to 40 % in IVF general patients [4,[25][26][27]. Bosch et al reported frequent premature luteinization and diminished PR with the introduction of a GnRH antagonist to their COH protocol for IVF in patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…as others have found that a subtle Prog rise has no negative effect on the pregnancy outcome [8,10,17] . The results are varied and may be due to methodological issues.…”
Section: Discussionmentioning
confidence: 79%
“…A subtle rise in serum progesterone (Prog) on the day of hCG administration is common and has been reported to occur in 5-35% of IVF cycles incorporating a GnRH agonist (GnRH-a) [7][8][9][10] or 20-38.3% with a GnRH antagonist for COH [11,12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian stimulation was done as previously described (Ubaldi et al, 1995). The combination of vaginal ultrasound results and serum oestradiol concentrations indicated that at least nine follicles were present (Vandervorst et al, 1998).…”
Section: Icsi Proceduresmentioning
confidence: 99%